Antinociceptive and Anti-oedematogenic Properties of Astilbin, Taxifolin and Some Related Compounds - Cechinel-Filho, Valdir; Vaz, Zulma Regina; Zunino, Luciano; Calixto, João Batista; Yunes, Rosendo Augusto (Arzneimittelforschung, 2000)
Astilbin (3-0-α-1-rhamnosyl-(2R,3R)-dihydroquercetin), the major constituent isolated from Hymeneae martiana and some derivatives obtained by structural modification, such as taxifolin and two related compounds, were evaluated as analgesics by using both writhing test and formalin test in mice. Their anti-oedematogenic actions were also analysed against paw oedema caused by carrageenan, dextran and bradykinin in rat. The results indicated that some compounds, such as taxifolin (2) and its tetramethylated derivative (4) exhibited potent and dose-dependent antinociceptive action against acetic acid-induced abdominal constriction when administered intraperitoneally or orally. They were more potent than acetylsalicylic acid and paracetamol (acetaminophen), two standard drugs used for comparison. Compounds 2 and 4 were also more potent than these drugs in attenuating to the second phase of the formalin-induced licking. Moreover, both compounds showed significant anti-oedematogenic effect, inhibiting the paw oedema formation induced by dextran. In contrast pentaacetylated taxifolin (3) was capable of inhibiting the paw oedema induced by bradykinin.
Keywords: Antiinflammatories; Astilbin, antinociceptive effect, derivatives; Hymenaea martiana; Taxifolin, antinociceptive effect